Visualization of defect densities in reduced graphene oxide - Eigler, Siegfried; Dotzer, Christoph; Hirsch, Andreas (Carbon, 2012)
Efficiently reducible graphene oxide (GO) was obtained, even if a high degree of functionalization is present. Graphite with few defects was used as starting material and oxidized according to Hummer's method. An extremely high I /I ratio for rGO of 2.8 (532 nm) was observed in the Raman spectrum as a consequence of the lower defect density in GO. It was also possible to demonstrate the impact of local defects on the structure in rGO by local laser exposure experiments on single graphene oxide flakes. Raman spectroscopy can visualize the laser impact by I /I ratio measurements. © 2012 Elsevier Ltd. All rights reserved.